Kegiatan Ekstrakurikuler Sebagai Wadah Pengembangan Bakat dan Minat Siswa - Hana Salsabila, Putri; Syaflita, Dina; Indriani, Novi (JURNAL ARMADA PENDIDIKAN, 2023)
Humans are born with innate abilities which are potentials that still need to be developed. Every human being has their own characteristics that can distinguish one human from another. With the existence of human abilities, it is demanded to be able to develop his potential so that he can become a quality and qualified human being. One way to hone these talents is through extracurricular activities with the aim that students' talents and creativity can be displayed to the fullest. The purpose of this study was to determine the effectiveness of these extracurricular activities as a forum for developing the talents and interests of the students of the Pekanbaru Bina Professional Vocational School. This research method is a qualitative method. The data collection technique used in this study is observation with data analysis techniques using interactive data analysis techniques. This extracurricular activity makes the students look so excited and enthusiastic. This is because students are given the freedom to be able to choose extracurricular activities that interest them. Extracurricular activities can be a success in exploring students' talents and interests.